Use of ivacaftor in late diagnosed cystic fibrosis monozygotic twins heterozygous for F508del and R117H-7T – a case report - Welsner, Matthias (BMC Pulm Med, 2019)
BACKGROUND: CFTR modulator therapy with ivacaftor is a treatment option for Cystic Fibrosis (CF) patients with at least one copy of a R117H-7T mutation in the CFTR gene. Desirable effects of this therapy are improvement of lung function, decrease in exacerbation rate, normalization or reduction of sweat chloride and weight gain. Monogenetic CF-twins carry identical genetic information, so therapy response and side effects are expected to be nearly identical under this specific therapy. CASE PRESENTATION: In monozygotic twins, at the age of 55, two pathogenic variants in the CFTR gene (F508del and R117H-7T) were detected. Both patients presented with a borderline sweat test (30–59 mmol/L) and despite the same genetic information and similar life circumstances the disease proceeds completely different. While one patient has severe pulmonary involvement with chronic P. aeruginosa infection, her twin sister is almost unimpaired. Liver or pancreatic involvement was not seen in either patient. Due to the presence of one copy of a R117H-7T mutation, CFTR modulator therapy with ivacaftor was initiated in both. Response and side effects were significantly different. In the less affected patient, we observed an improvement in lung function and a normalization of sweat chloride. In the severely affected patient, no functional response to treatment was seen, but stabilization of the disease state with a decrease in exacerbation and hospitalization rate and weight gain as well as a normalization of sweat chloride. There was an increase in liver enzymes in the less affected patient, which normalized after halving the dose of ivacaftor, while the therapeutic effect was maintained. CONCLUSIONS: Despite nearly identical genetic information, as in monogenetic twins, therapy response and onset of side effects of CFTR modulating therapy are very different. In patients with late diagnosis and severe pulmonary involvement, ivacaftor does not seem to improve lung function, whereas in patients with late diagnosis and low disease severity a relevant therapy response was obtained. In addition to lung function, additional clinical parameters such as reduction of exacerbation and hospitalization rate and weight gain should be used to assess therapy response, especially in severely affected patients.